A study of investigate and eliminate the crack-like flaws in bulk metal forming processes - Topa, Ameen; Shah, Qasim Hussain (IIUM Press, 2015)
An important concern in metal forming is whether the desired deformation can be accomplished without defects in the final product. Various ductile fracture criteria have been developed and experimentally verified for limited cases of metal forming processes. These criteria are highly dependent on the geometry of the workpiece and cannot be utilized for complicated shapes without prior experimental verification. However, experimental work is a resource hungry process. This paper proposes the ability of finite element analysis (FEA) software such as LS-DYNA to pinpoint the crack-like flaws in bulk metal forming products. Two different approaches named as Arbitrary Lagrangian-Eularian (ALE) and smooth particle hydrodynamics (SPH) formulations were adopted. The results of the simulations agree well with the experimental work and a comparison between the two formulations has been carried out. Both approximation methods successfully predicted the flow of workpiece material (plastic deformation), however ALE method was able to pinpoint the location of the flaws. The finite element simulation reveals that the uneven thickness of the product disturbs the plastic flow of the material resulting in the formation of the flaws. Corrections in the design of the die and tool have been made. The application of these corrections in the finite element simulations eliminated the occurrence of flaws in the finite element simulations. A parametric study was carried out to investigate the effects of strain rate, temperature, and friction forces on the stress and strain levels, which are the dominant contributing factors to the initiation of microvoids.